INITIAL EVALUATION OF GROWTH CONDITIONS OF MICROORGANISMSBIODEGRADATION OF NATURAL RUBBER - Nguyen Viet Thuy; Tran Thi Ung (Journal of Applied Science and Technology, 2019)
Natural rubber is a polymer that is resistant to abrasion and tear. It is widely used in making basic materials for the production of tires, rubber gloves, foam products, etc. Along with the expansion of production waste and waste rubber need to take measures. However, measures such as covering, burning and recycling rubber are difficult and less environmentally friendly. Therefore, bioprocessing is one of the most effective and environmentally friendly pathways. However, for biological treatment, the selection of microorganisms is of paramount importance and the use of native varieties will address the adaptation of microorganisms to new habitats and may Apply immediately to practice to reduce the process of surveying growth and development.With the source extracted from the enrichment tank and the wastewater, waste latex and waste sludge samples collected from a rubber processing from Cam Thuy - Thanh Hoa rubber factory, the research team isolated two strains E1 and E2 from the enrichment tank. At the same time from 2 isolates we went to study to investigate growth conditions to obtain the best biomass of each strain in the culture environment.